The “Syllabus Theological Pendulum” - HORVÁTH, Levente; KURTA, József (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The Transylvanian Reformed theologians of the late seventeenth century were constrained by Cartesian philosophy and may be said to represent the orthodox theology of contemporary Calvinism. In 1673, at the Synod of Radnót (Iernut), János Pósaházi, a Hungarian minister and Principal of the Reformed Theological Seminary, allied himself with Reformed Bishop Mihály Tófeus and presented his Syllabus of 76 theses to refute the theology of Cocceius, a famous Cartesian theologian of the Netherlands. Cocceius became known for developing federal (or covenant) theology, based on the rationalistic principles of Descartes, which were questioned by the Dutch Gisbertus Voetius, the famous contemporary orthodox Calvinist thinker of the times. Both Cocceius and Voetius and their successive students were mentors of Pósaházi, and for a whole generation of Transylvanian pilgrims who studied in the Low Countries during that century. Pósaházi’s Syllabus gained significance amid a theologically relevant controversy, in a historically, as much as a philosophically, crucial moment, in the philosophical milieu of Transylvania specifically and Hungary in general. This historical moment coincides with the Cartesian theory of the conservation of momentum. We can see the discussion of both the Cartesian and the Pascalian ego being dealt with in the philosophical and theological discourse of the time. With Descartes, there developed both a brand-new rationalism and idealism on the one hand and, with Pascal, a metaphysical existentialism and personalism on the other. Both of those orientations – whether directly or indirectly – heavily influenced successive theological developments, especially in the realms of the Reformed churches of both the Netherlands and Hungary, and Transylvania in particular.